Estimating the effectiveness of vaccine programs in dog populations. (2019) - Wallace, R.M.; Undurraga, E.A.; Gibson, A.; Boone, J.; Pieracci, E.G.; Gamble, L.; Blanton, J.D.
Abstract: Dogs harbor numerous zoonotic pathogens, many of which are controlled through vaccination programs. The delivery of these programs can be difficult where resources are limited. We developed a dynamic model to estimate vaccination coverage and cost-per-dog vaccinated. The model considers the main factors that affect vaccination programs: dog demographics, effectiveness of strategies, efficacy of interventions and cost. The model was evaluated on data from 18 vaccination programs representing eight countries. Sensitivity analysis was performed for dog confinement and vaccination strategies. The average difference between modelled vaccination coverage and field data was 3.8% (2.3%–5.3%). Central point vaccination was the most cost-effective vaccination strategy when >88% of the dog population was confined. More active methods of vaccination, such as door-to-door or capture-vaccinate-release, achieved higher vaccination coverage in free-roaming dog populations but were more costly. This open-access tool can aid in planning more efficient vaccination campaigns in countries with limited resources.